Mine Closure in a War Devastated Environment — A Case Study - McGann, MP; Jackson, RT (Mine Closure 2008: Proceedings of the Third International Seminar on Mine Closure, 2008)
Like most mining operations, closure planning and execution at Lane Xang Minerals Limited’s Sepon site (located in the Lao PDR) must consider issues such as acid mine drainage, surface water management, erosion control and socio-economic sustainability. However, while addressing those issues, it must also establish an acceptable post-mining land use and ensure that work areas are safe. At the Sepon site, which was heavily bombed during the second Indochina war, the selection of a post-mining land use is not as simple as the often stipulated condition ‘to return the land to its pre-mining use’. Furthermore the presence of considerable quantities of unexploded ordinance (UXO) makes the task of site rehabilitation more challenging. However, this also creates some unusual opportunities.